Ethnic Memory And Historical Injustices In Nigeria - Olusegun, Atere Clement (Advances in Social Sciences Research Journal, 2020)
It is a known fact that not few Nigerians believed that the country has committed atrocities against her citizen and this has caused mutual suspicion, deep divisions, inter-ethnic wrangling, and unending disputations in this ethnically and geographically diverse nation. The aim of this paper is to provide fresh insight on the causality of the deep mistrust and mutual suspicion among the various ethnic groups which in turn has caused the Nigeria nation much needed unity. The paper argued that recurring memorialization of unresolved historical injustices has been a potent poison to the glowing of communal and organic wellbeing of the nation. The paper concluded that the government must redress the past historical injustices, explore how Nigerians together can search for common memories to meet present needs, and allow the various ethnic group to come to terms with their past. The paper recommended new Truth and Reconciliation Commission